Traffic Sign Detection and Classification for Driver Assistant System - Md Ghazaly, Mariam; Mohd Ali, Nursabilillah; Mohd Sobran, Nur Maisarah; Ab. Shukur, Syahar Azalia; Tuani Ibrahim, Ahmad Fayeez (2014)
The present paper describes the Traffic Sign Detection and Classification for Driver Assistant System